Effects of Experimental Releases of Oil and Dispersed Oil on Arctic Nearshore Macrobenthos. I. Infauna - Cross, William E.; Thomson, Denis H. (ARCTIC, 1987)
An experimental subsurface release of chemically dispersed oil at Cape Hatt, northern Baffin Island, resulted in short-term, relatively high oil concentrations in the waters of two adjacent bays, whereas untreated oil released onto the surface of a third bay could not be detected in the water below a depth of 1 m. Diver observations revealed no apparent short-term effects of untreated oil on shallow water infauna, whereas marked acute effects on infauna, including emergence from the substrate and narcosis, were apparent in the dispersed oil bays within 24 h of the release. Analysis of systematic airlift samples at two depths (3 and 7 m) in the three test bays and a fourth (reference) bay during the open water seasons of 1980-83 (two pre-spill and four post-spill sampling periods) showed that most affected animals recovered. Neither type of oil release caused any large-scale mortality of benthic infauna. Multivariate analyses showed no significant change in infaunal community structure, and effects attributable to oil were found in only 3 of 72 univariate analyses of density, biomass or size data for individual taxa. A progressive decrease in the condition of the filter-feeding bivalve Serripes groenlandicus in the reference bay (several km distant from the dispersed oil release) was apparently the result of exposure to dilute dispersed oil for several days. A similar effect on condition in the surface deposit-feeding bivalve Macoma calcarea was apparently caused by relatively low oil concentrations in the sediments of the dispersed and surface oil release bays. There were no apparent effects on recruitment in bivalve species with planktonic larvae, but density changes in the polychaete Spio spp. indicated that oil in the sediments of the surface oil release and dispersed oil release bays affected reproductive processes. Effects on the condition of the bivalves and on Spio spp. were still evident two years post-spill in 1983, the last year of sampling.Key words: arctic infauna, oil effects, dispersed oil effects, ...